1986
DOI: 10.1042/bj2340523
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of fibrinogen by casein kinase 2

Abstract: Casein kinase 2 from rat liver cytosol phosphorylated human fibrinogen in a reaction that was not stimulated by Ca2+ or cyclic AMP, but was markedly inhibited by heparin, and proceeded at a similar rate when either ATP or GTP was used as phosphate donor. Analysis of casein kinase 2 by glycerol-density-gradient centrifugation showed that the activities towards fibrinogen, casein, phosvitin, high-mobility-group protein 14 and glycogen synthase coincided. Maximal incorporation into fibrinogen by casein kinase 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The most likely and unique candidate for phosphate incorporation within this region (amino acid region 680 -709) is Ser 692 . These data are consistent with previous findings (21) and clearly demonstrate that factor Va heavy chain is a physiological substrate for platelet-mediated phosphorylation as is also the case for fibrinogen (45).…”
Section: Ckii-mediated Phosphorylation Of Human Factor V Localizationsupporting
confidence: 93%
“…The most likely and unique candidate for phosphate incorporation within this region (amino acid region 680 -709) is Ser 692 . These data are consistent with previous findings (21) and clearly demonstrate that factor Va heavy chain is a physiological substrate for platelet-mediated phosphorylation as is also the case for fibrinogen (45).…”
Section: Ckii-mediated Phosphorylation Of Human Factor V Localizationsupporting
confidence: 93%
“…The remaining peptides consisted of the three FPA fragments: FPA -70%, FPA-P -20%, desAla FPA -10% (21). Previous studies with fibrinogen have demonstrated that phosphorylation of the Aa chain serine, a post-translational modification occurring prior to secretion from the liver (22)(23)(24), and removal of the amino-terminal alanine from the Aa chain are regulated with respect to subject parameters, such as age, trauma, or illness (24)(25)(26)(27), and are in place on fibrinogen prior to thrombin action (22)(23)(24). The low levels of FPA present in EDTA plasma can be attributed to the expectedly minimal thrombin activity in vivo and minimal ex vivo thrombin activation accomplished by calcium sequestration by EDTA.…”
Section: Fpa Peptides In Serummentioning
confidence: 99%
“…The protein tyrosine kinase (~40) was purified from bovine thymus as described by Zioncheck et al [32]. Casein kinase-1 was obtained from rat liver cytosol as indicated in [34].…”
Section: Enzyme Purification and Assaymentioning
confidence: 99%